Analisis Opini Siswa Kelas X SMA 4 Tangerang Selatan Terhadap Pembelajaran Bahasa Indonesia di Sekolah - Ismi Nur Aliya; Hilwa Tsamarah; Deva Azzahra Aditiya; Muhammad Daffa Alghifari; Mahmudah Fitriyah ZA (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
The purpose of this study was to determine the ability to write opinion texts of SMA 4 Tangerang Selatan students on learning Indonesian at school. The researcher created a questionnaire containing questions regarding the implementation of Indonesian language learning at SMA 4 Tangerang Selatan. This research was sourced from class X SMA 4 South Tangerang as many as 32 students as respondents. The research data used is the opinion of class X students of SMA 4 South Tangerang. The source of the research data is the opinion of the questionnaire. Data collection techniques using observation, note taking, documentation, and questionnaire techniques. Research analysis techniques use qualitative content analysis techniques, namely data analysis techniques or methods to study and analyze communication systematically, objectively and qualitatively. The skills of writing opinions of class X SMA Tangerang Selatan students on learning Indonesian at school provide many facts and can also be used as material for evaluating learning in class in the future. The number of students who liked Indonesian was more than the number of students who did not like it, namely 72%. The students' opinion about teacher teaching that they feel is that there are teachers who teach but are less varied, namely only focusing on theory but not often practicing so that students quickly get bored. Learning material that students find difficult is figurative material. Fun learning for students is learning that includes games